Using remote sensing techniques to evaluate lining efficacy of watercourses - Sakthivadivel, Ramaswamy; Amarasinghe, Upali A.; Thiruvengadachari, S. (International Water Management Institute, 2001)
Studies the low-cost alternative strategy of selective lining of watercourses to reduce seepage and increase irrigated areas in the Indian subcontinent. Satellite remote-sensing (SRS) is seen as a cost-effective evaluation tool in view of its large area of synoptic and repetitive coverage.